2009
DOI: 10.1080/09544820701564465
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the strategic objectives between new product development and product design in Taiwan's information industry

Abstract: This study explores the strategic groups developed from the new product development strategies of various firms in the Taiwanese information industry. The product design strategies of the surveyed companies and the mappings the strategic objectives between product design and new product development are discussed. Based on the questionnaire survey and interviews, in terms of the new product development strategy for dealing with global marketing competition, enterprises in the Taiwanese information industry can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…can improve problem-solving skills of project team members in a distributed environment and enhance the pursuit of knowledge within distributed organisations. Many authors have provided advice on the practical implementation of CPD (Chu and Cheng, 2005;Graber, 1996;Hsu, 2009;Ichijo and Kohlbacher, 2008;Rodriguez and Al-Ashaab, 2005;Wu, 2007). However, for the achievement of high performance in distributed environments, three soft dimensions are more important than points 1 to 4 above (Salomo et al, 2010).…”
Section: Organisational Viewmentioning
confidence: 99%
“…can improve problem-solving skills of project team members in a distributed environment and enhance the pursuit of knowledge within distributed organisations. Many authors have provided advice on the practical implementation of CPD (Chu and Cheng, 2005;Graber, 1996;Hsu, 2009;Ichijo and Kohlbacher, 2008;Rodriguez and Al-Ashaab, 2005;Wu, 2007). However, for the achievement of high performance in distributed environments, three soft dimensions are more important than points 1 to 4 above (Salomo et al, 2010).…”
Section: Organisational Viewmentioning
confidence: 99%
“…If companies do not actively engage in product innovation activities, they will eventually be eliminated from the market because their products will not be in line with the trend [21]. Therefore, in order to maintain a competitive advantage, the R&D departments and product designers of these companies must continuously respond to the challenges of the changing market environment [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Yoo [24] argued that the competitiveness of enterprises depends on their ability to utilize technological resources or differences in response to changes, as well as the scale of resources and technologies they possess. In a study of home appliances, Hsu [23] found that there is a relevant design strategy for home appliance manufacturers to design and innovate their products in response to technological changes. Most previous innovation studies were conducted from management and economics perspectives, while the correlation between product innovation and design strategy and the operation mode of home appliance products has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Organisations that manufacture homogeneous goods for example, paper, agricultural products, and energy are restricted by the fact that their consumers perceive their product as being similar (Hwang et al, 2008). Such organisations encounter difficulties in differentiating themselves, and in uniquely positioning their products (Arping and Lóránth, 2006;Boyaci and Ray, 2006;Hsu, 2009;Damanpour, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Even in the most unglamorous industries, however, innovation management remains of central importance. Because successful differentiation allows the innovator to create and capture market share (Arping and Lóránth, 2006;Hsu, 2009), and to generate superior profits (Besanko et al, 2012). The milk company, for example, that innovates upon its product by adding flavor can create a new market, a new revenue stream, and a dominant position.…”
Section: Introductionmentioning
confidence: 99%